Pengaruh Latihan Variasi Plyometric terhadap Peningkatan Kemampuan Vertical Jump pada Atlet Putra Klub Bola Voli Usia Remaja - Imandaqurani, Deva; Pratama, Henri Gunawan (MAN Insan Cendekia Jambi, 2024)
The jump smash technique relies on the strength of the leg muscles. Leg muscles are the most important muscle group that supports jumping. Plyometric is a type of exercise that forces muscles to work quickly. Volleyball athletes must use different plyometric training methods before performing vertical jumps. The research method used a